PENERAPAN MODEL KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SDN 003 BANGKINANG KOTA - Rizki Ananda (Universitas Negeri Medan, 2017)
Abstract: Implementation of Numbered Head Together (NHT) Co-operative Model to Improve Student's IPS Learning Outcomes in Grade IV SDN 003 Bangkinang Kota. This type of research is classroom action research. This research uses qualitative approach. This study was conducted in two cycles, conducted by collaboration between researchers and teachers. Subjects in this study were students of grade IV SD 003 Bangkinang Kota which amounted to 30 people. The results of the first cycle of the test before the learning average of the students score 5.94 and the final test of students' learning completeness reached 56.7%, while the final test of the second cycle of student learning completeness score increased to 80%. Based on the observation result seen improvement of students understanding after the learning process which is depicted from result of student test. p-ISSN: 2355 - 1739e-ISSN: 2407 - 6295 p-ISSN: 2355 - 1739e-ISSN: 2407 - 6295 Keywords:Cooperative Learning Model Numbered Head Together (NHT), Learning Outcomes, Social Sciences Abstrak : Penerapan Model Kooperatif Tipe Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SDN 003 Bangkinang Kota. Jenispenelitianiniadalahpenelitiantindakankelas (classroom action research). Penelitianinimenggunakanpendekatankualitatif. Penelitianinidilaksanakandalamduasiklus, dilakukandengancarakolaborasi antarapenelitidan guru. Subjekdalampenelitianiniadalahsiswa kelas IV SD 003 Bangkinang Kota yang berjumlah 30 orang. Hasilpenelitiansiklus I tesawalsebelum pembelajaran rata-rata nilaisiswa 5,94 danpadatesakhir ketuntasan belajar siswa mencapai56,7 %, sedangkantesakhirsiklus II nilaiketuntasan belajar siswa meningkatmenjadi80 %. Berdasarkanhasilpengamatanterlihatpeningkatanpemahaman siswa setelah proses pembelajaran berlangsung yang tergambar dari hasil tes siswa. Kata Kunci :Model Pembelajaran Kooperatif tipe Numbered Head Together (NHT) Hasil Belajar, Ilmu Pengetahuan SosialAbstract: Implementation of Numbered Head Together (NHT) Co-operative Model to Improve Student's IPS Learning Outcomes in Grade IV SDN 003 Bangkinang Kota. This type of research is classroom action research. This research uses qualitative approach. This study was conducted in two cycles, conducted by collaboration between researchers and teachers. Subjects in this study were students of grade IV SD 003 Bangkinang Kota which amounted to 30 people. The results of the first cycle of the test before the learning average of the students score 5.94 and the final test of students' learning completeness reached 56.7%, while the final test of the second cycle of student learning completeness score increased to 80%. Based on the observation result seen improvement of students understanding after the learning process which is depicted from result of student test. p-ISSN: 2355 - 1739e-ISSN: 2407 - 6295 p-ISSN: 2355 - 1739e-ISSN: 2407 - 6295 Keywords:Cooperative Learning Model Numbered Head Together (NHT), Learning Outcomes, Social Sciences Abstrak : Penerapan Model Kooperatif Tipe Numbered Head Together (NHT) untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SDN 003 Bangkinang Kota. Jenispenelitianiniadalahpenelitiantindakankelas (classroom action research). Penelitianinimenggunakanpendekatankualitatif. Penelitianinidilaksanakandalamduasiklus, dilakukandengancarakolaborasi antarapenelitidan guru. Subjekdalampenelitianiniadalahsiswa kelas IV SD 003 Bangkinang Kota yang berjumlah 30 orang. Hasilpenelitiansiklus I tesawalsebelum pembelajaran rata-rata nilaisiswa 5,94 danpadatesakhir ketuntasan belajar siswa mencapai56,7 %, sedangkantesakhirsiklus II nilaiketuntasan belajar siswa meningkatmenjadi80 %. Berdasarkanhasilpengamatanterlihatpeningkatanpemahaman siswa setelah proses pembelajaran berlangsung yang tergambar dari hasil tes siswa. Kata Kunci :Model Pembelajaran Kooperatif tipe Numbered Head Together (NHT) Hasil Belajar, Ilmu Pengetahuan Sosial